Refugees and Asylum Seekers in Indonesia Amid the Spread of COVID-19: Case Study of Refugees and Asylum Seekers in Pekanbaru - Rizky Octa Putri Charin (Universitas Diponegoro, 2021)
This paper aims to analyze how the Indonesian government’s efforts to fulfill the health rights of refugees or asylum seekers who were in Indonesia when the COVID-19 case hit the world. Pekanbaru was chosen as a case study because it has broken the record for the highest number of additional COVID-19 cases in Indonesia. This condition is exacerbated by the fact that, Pekanbaru is also one of the cities with the highest number of receiving refugees in Indonesia. Using qualitative research methods, this paper argues that the acceptance of refugees by Indonesia on humanitarian principles is in line with the identity that has been shown as defenders of human rights. To maintain this identity, in terms of handling COVID-19 with refugees, it would be better if Indonesia adapted policies that were adaptive and sensitive to minority groups, in this case asylum seekers in Pekanbaru.